THE DETERMINANTS OF TAX EVASION BY CORPORATE TAXPAYERS (A STUDY ON THE CORPORATE TAXPAYERS REGISTERED AT THE MEDIUM TAX OFFICE OF SURABAYA) - Theresa Anggraeni (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
This study aims at identifying the determinants of tax evasion by corporate taxpayers registered at the Medium Tax Office of Surabaya. The data are analyzed through multiple linear regression by using SPSS software. The results of the hypothesis testing indicate that tax sanction has effect ontax evasion, while taxation systems, tax rates, accuracy of tax utilization, and taxation technology and information have no effect on tax evasion. It implies that the lower the tax sanctions, the less likely a tax evasion occurs, and vice versa. Keywords : taxation systems, tax rates appropriate tax allocation, tax sanctions, taxation technology and information, tax evasion